THE BRANDING OF ETHICS: A Multidisciplinary Investigation into the Ethical Branding Phenomenon in the UK - Zhang, Lifu (2006)
Ethical considerations are a potentially powerful influence on consumer purchasing decisions. Marketers have begun to recognize the need to incorporate business ethics into their marketing activities. The practice of 'ethical branding' is a relatively new phenomenon and previous studies have been mainly focusing on how consumers make sense of it, rather than how and why marketers position their products as ethical brands. This study aims to explore the motives behind ethical branding decisions and the ways in which ethical brands function, by adopting a multidisciplinary approach combining perspectives from marketing and cultural studies. The review of the marketing literature describes the changing nature of marketing, entry barriers, consumer pressure, and business performance as key determinants in marketers' decision-making process with regard to ethical branding. The focus of this study lies in the contribution of cultural studies to the ongoing debate. It highlights the significance of identity, power, and meaning in understanding ethical brands and provides an analysis of various advertisements and marketing campaigns, using cultural studies research methods, in order to explain how products can be marketed as ethically conscious commodities.